Introducing the term 'Biocontrol Plants' for integrated pest management - Parolin, Pia (2014)
Studies of interactions between crops, additional plants, pests and beneficial organisms already exist as well as studies of natural enemy preference, dispersal, and abundance. However, these studies focus on tri-trophic interactions from an "arthropod" point of view. We think that in order to optimize crop protection methods we need to understand the effects that plant structures have on the various arthropods and on subsequent tri-trophic interactions. Although studies and reviews describing the role of secondary plants in Integrated Pest Management (IPM) exist, to date a general term which encompasses all plants added to a cropping system with the aim of enhancing IPM strategies has yet to be formulated. Therefore, we suggest a new term, "biocontrol plants", which we define as plants that are intentionally added to a crop system with the aim of enhancing crop productivity through pest attraction and/or pest regulation; a term that will promote the use of biocontrol services, and can ultimately lead to an increase in the sustainability of cropping systems.